2015
DOI: 10.1155/2015/893013
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Management of Radiation-Induced Nausea and Vomiting

Abstract: The incidence of nausea and vomiting after radiotherapy is often underestimated by physicians, though some 50–80% of patients may experience these symptoms. The occurrence of radiotherapy-induced nausea and vomiting (RINV) will depend on radiotherapy-related factors, such as the site of irradiation, the dosing, fractionation, irradiated volume, and radiotherapy techniques. Patients should receive antiemetic prophylaxis as suggested by the international antiemetic guidelines based upon a risk assessment, taking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 39 publications
1
18
1
Order By: Relevance
“…The RINV was seen among 53.1% of the patients. Feyer et al [ 11 , 12 ] have reported a range of 50% to 80% RINV in RT depending on the RT site, 2 to 3 weeks after the onset of treatment, which is in agreement with our study. The Italian prospective observational trial on emesis in RT reported a 27.9% incidence of both vomiting and nausea, 27.1% vomiting, and 11% nausea among 1004 patients.…”
Section: Discussionsupporting
confidence: 93%
“…The RINV was seen among 53.1% of the patients. Feyer et al [ 11 , 12 ] have reported a range of 50% to 80% RINV in RT depending on the RT site, 2 to 3 weeks after the onset of treatment, which is in agreement with our study. The Italian prospective observational trial on emesis in RT reported a 27.9% incidence of both vomiting and nausea, 27.1% vomiting, and 11% nausea among 1004 patients.…”
Section: Discussionsupporting
confidence: 93%
“…26 Subsequently, Fan et al have reported a higher incidence of nausea (91%) and vomiting (59%) in patients with head and neck cancer treated with IMRT irrespective of concurrent cisplatin-based chemotherapy. A prospective observational trial demonstrated that radiation-induced emesis occurred in 40% of head and neck patients treated with conventional radiation techniques.…”
Section: Incidence Data and Predictor Factors Of Rinvmentioning
confidence: 99%
“…Field size, location, and fractionation schedule are thought to be important factors associated with development of nausea and vomiting. 26 Subsequently, Fan et al have reported a higher incidence of nausea (91%) and vomiting (59%) in patients with head and neck cancer treated with IMRT irrespective of concurrent cisplatin-based chemotherapy. 27 There is shortage of data on this topic, and the lack of randomized controlled trials on RINV in patients with HNSCC treated with IMRT makes it difficult to estimate the real incidence of RINV in this setting.…”
Section: Incidence Data and Predictor Factors Of Rinvmentioning
confidence: 99%
“…Nausea and vomiting are common symptoms in patients with cancer . The overall incidence of nausea and vomiting in patients with cancer is difficult to estimate because a large number of treatment‐, disease‐, and patient‐related factors affect the risks of these events .…”
Section: Nausea and Vomiting In Patients With Cancer—incidence And Cumentioning
confidence: 99%